Analysis of the Impact of Technological Innovation and Design Creativity on the Attractiveness of Tourism Destinations in Bali - I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi; Made Darmiati; Nyoman Gede Mas Wiartha; Luh Putu Citrawati; Made Yudhawijaya (Westscience Press, 2024)
This research investigates the impact of technological innovation and design creativity on the attractiveness of tourism destinations in Bali. A quantitative approach was employed, collecting data from 267 tourists visiting various destinations in Bali. Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis was used to analyze the relationships between technological innovation, design creativity, and destination attractiveness. The results revealed significant positive relationships between technological innovation and destination attractiveness (β = 0.543, p < 0.001) and between design creativity and destination attractiveness (β = 0.486, p < 0.001). The model fit assessment indicated satisfactory fit indices for the SEM-PLS model. Overall, the findings highlight the importance of leveraging technological innovation and design creativity to enhance the attractiveness of tourism destinations in Bali and foster sustainable tourism growth.